2015
DOI: 10.2106/jbjs.cc.n.00082
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Dislocation of the Pubic Symphysis with an Open Reduction and Anterior and Posterior Pelvic Ring Fixation

Abstract: This case report is a valuable addition to the current literature on ODPS because we believe it to be the first report describing a patient who required both anterior and posterior fixation because of pelvic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…There have been a few techniques and approaches used to reduce and stabilize these injuries in the literature. The standard treatment is usually through an open reduction using a Pfannenstiel incision, followed by pubic symphyseal plating for stabilization [16][17][18][19][20][21][22][23][24][25] . Alternatively, these injuries can be open reduced through the same approach, but then stabilized with an external fixator instead of plating 1,26 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few techniques and approaches used to reduce and stabilize these injuries in the literature. The standard treatment is usually through an open reduction using a Pfannenstiel incision, followed by pubic symphyseal plating for stabilization [16][17][18][19][20][21][22][23][24][25] . Alternatively, these injuries can be open reduced through the same approach, but then stabilized with an external fixator instead of plating 1,26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, not all locked pelvis can be reduced using closed methods.This condition is also associated with other concomitant injuries due to the forces required to dislocate the symphysis. It is mandatory to rule out bladder injury in every case, as the associated urogenital injuries have been reported up to 47% [4].All of the reported cases showed that patient either have urogenital injury or concomitant pelvic fracture. This patient had a urinary catheter inserted at the emergency department and the urine remained clear throughout the admission.…”
Section: Discussionmentioning
confidence: 99%